Analisis Efisiensi dan Skala Ekonomis Pada Industri Kerajinan Anyaman Bambu Kecamatan Susut Kabupaten Bangli - Taranitha Putri Wilanda; Surya Dewi Rustariyuni (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2019)
This study aims to analyze; 1) simultaneously, and analyze the partial effect of the use of production factors labor, work experience and capital for various products of the bamboo weaved craft industry, 2) to investigate the economies of scale and 3) analyze the efficiency of production factors in the bamboo weaved handicraft industry in Kecamatan Susut, Kabupaten Bangli. The type of data in this study is quantitative and qualitative data with primary and secondary data sources. Respondents in this study amounted to 93 peoples, a sample of 1277 craftsmen and calculated using the Slovin's formula. The determination of the sample size in each village was determined by the disproportional stratified random sampling method. Data analysis techniques used in this research is the analysis techniques of Cobb-Douglass, economies of scale, and economic efficiency. The results showed that the variable labor (X1), work experience (X2), and capital (X3) simultaneously and partially had a positive and significant impact on the amount of production (Y) to the bamboo weaved craft industry in Susut District, Bangli Regency. Economies of scale test in a state of increasing return to scale, but partially still in a decreasing return to scale condition. The efficiency of the use of production factors has not been efficient.